Preliminary Exploration of Training, Perspectives, and Mental Health Program Awareness in Slaughter Plant Workers Who Perform Stunning as Part of Their Job - Edwards-Callaway, Lily N. (Journal of applied animal ethics research, 2022)
Abstract Stunning livestock (rendering them unconscious) is a necessary component of initiating humane slaughter, thus it is important to provide support to individuals performing this job. The objective of this study was to identify worker perspectives, training methods, and resources available to workers performing stunning. An online survey was distributed to industry association listservs or direct emails of slaughter plants in the United States of America. An additional survey was administered at an industry conference to increase participation. Twenty respondents completed the slaughter survey. Respondents were commonly trained using an in-person, in-house trainer. Respondents indicated feeling confident in performing stunning after training (18, 90%) and that “stunning animals has become easier the more times they did it” (17, 85%). Only 2 (10%) respondents said there were aware of programs to promote mental health, but most (17, 85%) felt “supported by peers in their workplace.” This preliminary survey identified interest in more training and limited awareness of supportive resources.